EVALUASI SISTEM INFORMASI AKADEMIK SATYA WACANA MENGGUNAKAN PIECES FRAMEWORK - Alexander Winandhito Adi; Evi Maria (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
The research objective is to evaluate the Satya Wacana Academic Information System (SIASAT) using the PIECES framework. The evaluation was carried out from the user side, namely Satya Wacana Christian University (SWCU) students, by assessing six variables: performance, information and data, economics, control, security, efficiency, and service. The PIECES framework has effectively identified problems, opportunities, and future system development directions. Research data was obtained by distributing questionnaires. Respondents to this study were SWCU students, with 202 respondents. Data was measured using a Likert scale. The evaluation results found that students felt delighted using SIASAT when assessed from the performance, efficiency, and service variables. While from the information and data variables, as well as economics, students feel satisfied. The lowest score is on the control and security variables; students are in the neutral category when assessing this variable. Slow handling when a server down occurs is why students give the lowest score, so SIASAT managers need to improve from the control and security side. Overall, the average score of SIASAT user satisfaction is 3.93. It means that SWCU students are satisfied when they use SIASAT to support academic administration activities while studying at SWCU.